2013
DOI: 10.1002/j.2161-1882.2013.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Cultural Attitudes Matter? The Role of Cultural Orientation on Academic Self‐Concept Among Black/African College Students

Abstract: The authors explored the relationship between academic self-concept and noncognitive variables (i.e., Africentric cultural orientation, academic class level, gender, and involvement in culturally relevant school and community activities) among Black/African college students. Results indicated that Africentric cultural orientation and academic class level were significantly related to academic self-concept. Female students had higher scores on the Academic Self-Concept Scale (Reynolds, Ramirez, Magrina, & Allen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Therefore, it is critical for school‐based practitioners and researchers to understand and incorporate issues of culture and racial aspects of socialization when studying Black youth development (Jones & Neblett, ; Worrell, ). The significant and practically meaningful gains in students’ Afrocentric world view were promising given the constructs related to positive outcomes in the empirical literature (Neblett, Seaton, Hammond, & Townsend, ; Williams & Chung, ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is critical for school‐based practitioners and researchers to understand and incorporate issues of culture and racial aspects of socialization when studying Black youth development (Jones & Neblett, ; Worrell, ). The significant and practically meaningful gains in students’ Afrocentric world view were promising given the constructs related to positive outcomes in the empirical literature (Neblett, Seaton, Hammond, & Townsend, ; Williams & Chung, ).…”
Section: Discussionmentioning
confidence: 90%
“…Their results showed that greater adherence to Afrocentric cultural values was predictive of higher levels of self‐esteem and perceived social support satisfaction. Williams and Chung () explored the relationship between academic self‐concept and noncognitive variables (i.e., Afrocentric cultural orientation, academic class level, and involvement in culturally relevant school and community activities). Results showed that Afrocentric cultural orientation and academic class level are significantly related to academic self‐concept.…”
Section: Identity Development and Black Youthmentioning
confidence: 99%
“…For Black students, some of the challenges that affected their persistence were overcome with support from a professional counselor or advisor (W. S. Williams & Chung, 2013).…”
Section: Services and Programsmentioning
confidence: 99%
“…Counseling and advising centers have created a positive atmosphere and provided ways to address challenges -such as academic adjustment, financial difficulty, living conditions, and study skill issues -that have caused Black male students to drop out (W. S. Williams & Chung, 2013). Although very little research has shown correlation between seeing a counselor and retention rates, it has shown that Black students who utilized a counseling center early in their college career were more successful because they could tackle pre-existing fears that affected their self-concept and self-esteem (W. S. Williams & Chung,20).…”
Section: Services and Programsmentioning
confidence: 99%
See 1 more Smart Citation